2017
DOI: 10.21053/ceo.2016.01263
|View full text |Cite
|
Sign up to set email alerts
|

Cytokeratin 13, Cytokeratin 17, and Ki-67 Expression in Human Acquired Cholesteatoma and Their Correlation With Its Destructive Capacity

Abstract: Objectives Cholesteatoma is a nonneoplastic destructive lesion of the temporal bone with debated pathogenesis and bone resorptive mechanism. Both molecular and cellular events chiefly master its activity. Continued research is necessary to clarify factors related to its aggressiveness. We aimed to investigate the expression of Ki-67, cytokeratin 13 (CK13) and cytokeratin 17 (CK17) in acquired nonrecurrent human cholesteatoma and correlate them with its bone destructive capacity.Methods A prospective quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
0
13
2
Order By: Relevance
“…That probably might suggest the specific stage of disease with a decrease in cellular activity. However, this data was different from other studies where Chung et al[35] and Hamed et al[36] proved overexpression of Ki-67 in cholesteatoma tissue compared to skin epithelium. This might be explained by the fact that Hamed and other authors took control skin from the same patients, who had cholesteatoma.…”
contrasting
confidence: 96%
“…That probably might suggest the specific stage of disease with a decrease in cellular activity. However, this data was different from other studies where Chung et al[35] and Hamed et al[36] proved overexpression of Ki-67 in cholesteatoma tissue compared to skin epithelium. This might be explained by the fact that Hamed and other authors took control skin from the same patients, who had cholesteatoma.…”
contrasting
confidence: 96%
“…Hereof we investigated its copy number variant with regard to cholesteatoma in patients with COM and we show the significant difference in allele frequency, with allele 2 predominance in COM patients with cholesteatoma. Molecular mechanisms and genetic basis of both, COM and cholesteatoma and their potential clinical aggressiveness are challenging subject in current research [ 33 ] and has yet to be resolved. Recently, an extensive review was published in order to gather existing literature regarding heritability of cholesteatoma [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating markers as indicators of the aggressive nature and bone destruction capacity have recently shown that some cholesteatomas overexpress Ki-67, a cell proliferation marker of tumors and non-neoplastic proliferative disorders that includes cholesteatoma. CK17, a marker of keratinocyte differentiation, has been shown to be a predictor of aggressiveness and invasive capability when present [45]. Hamed et al observed that overexpression of both markers were seen in the epithelial portion of cholesteatoma in cases of invasive cholesteatoma where severe ossicular destruction was present whereas, the non-invasive group expressed each marker in an inactive form [45].…”
Section: Histopathologic Findingsmentioning
confidence: 99%
“…CK17, a marker of keratinocyte differentiation, has been shown to be a predictor of aggressiveness and invasive capability when present [45]. Hamed et al observed that overexpression of both markers were seen in the epithelial portion of cholesteatoma in cases of invasive cholesteatoma where severe ossicular destruction was present whereas, the non-invasive group expressed each marker in an inactive form [45].…”
Section: Histopathologic Findingsmentioning
confidence: 99%